The reality of sports marketing in the Republic of Yemen: A comparative study between team and individual sports - hocine nacer al sofi, bakil; Mahdi Al-Houri, Mohammed (sports creativity, 2025)
The study aims to understand the reality of sports marketing in the Republic of Yemen, to examine the differences in the marketing process according to team and individual sports, and to identify the main obstacles and difficulties facing sports marketing in clubs. It relied on the descriptive method (survey method) and was conducted on a sample of 214 clubs (represented by the Secretary-General) in the Republic of Yemen. The study reached the following findings: The reality of sports marketing does not meet the aspirations of the sports community in the Republic of Yemen. The reality of sports marketing in Yemen differs according to the type of sport (team or individual). The main obstacles or difficulties facing the activation of sports marketing in sports clubs in Yemen are as follows: the lack of stadiums and covered sports halls meeting international standards in sports clubs; the inability of sports clubs to host Arab and international team and individual games; Yemeni sports lack a wide fan base; private companies do not prioritize attention to the sports field; the absence and shortage of economic institutions supporting sports; Yemen is characterized by a strongly tribal nature. Which makes them uninterested in practicing or watching sports. Weak level of athletic achievement in most games. Lack of autonomy of sports clubs as they are affiliated with the Ministry of Youth and Sports. The absence of marketing departments in sports clubs.